CURRENT SPECIES COMPOSITION OF ICHTHYOFAUNA OF THE DUKENTSAY RIVER (Scientific journal of the Fergana State University, 2024)
Dukentsay is one of the right tributaries of the Akhangaran River, flowing from the Chatkal Mountain Range. The article provides preliminary data about the species composition of the fish fauna of the Dukentsay River. Based on the ichthyological observations carried out in Dukentsay, the following species were recorded: Triplophysa elegans, Iskandaria kuschakewitschi, Schizothorax eurystomus and Glyptosternon oschanini. No acclimatized or accidentally introduced fish species were recorded. The study of the ichthyofauna of mountain rivers such as Dukentsay plays an important role in understanding the mechanisms of the formation of ichthyocenosis of mountain rivers.